Clinical and Neurophysiological Features of Vincristine-Induced Peripheral Neuropathy in Indonesian Children with Acute Lymphoblastic Leukemia - Raden Muhammad Indra; Irsan Saleh; Irawan Mangunatmadja; Yulia Iriani; Zen Hafy; Dian Puspitasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Vincristine-induced peripheral neuropathy (VIPN) is a common complication clinical pattern vary across populations, and data from Indonesian children remain limited. Objectives to describe the clinical and nerve conduction study (NCS) features of VIPN in children with ALL treated at a tertiary hospital in Indonesia. We conducted a cross-sectional study of children with ALL receiving chemotherapy recruited consecutively at Mohammad Hoesin Hospital, Palembang, from November 2023 to August 2025. Data were collected from detailed neurological and NCS examinations. Diagnosis of VIPN was made using NCS. Severity was graded using the Common Terminology Criteria for Adverse Events (CTCAE v5.0). Clinical features and NCS findings were evaluated. Comparisons were made between induction and maintenance phases, including the proportions of severity groups, clinical symptoms, individual nerve involvements, number of symptoms and nerves, as well as the type of lesions. A total of 118 children were enrolled; 65 (55.1%) had VIPN by NCS criteria. Neuropathy incidence was similar in induction (56.9%) and maintenance (52.8%) phases (p=0.66). Most cases were CTCAE grade 2–3. Weakness was the most frequent symptom (56.9%), while paresthesia was significantly more common in the induction phase (p=0.008). Peroneal motor nerve involvement was the most frequent NCS abnormality (91.1%), followed by median motor (50.0%) and ulnar nerves (33.7%). The induction phase was characterized by additional upper extremity nerve involvement compared to the maintenance phase, including the median (p=0.004) and ulnar (p=0.025) nerves. Sural sensory nerve abnormalities were significantly more prevalent during the maintenance phases (p=0.002). All cases demonstrated axonal, motor-predominant neuropathy, with no isolated sensory cases. VIPN is highly prevalent among Indonesian children with ALL, with motor-predominant, axonal involvement. The induction phase has more widespread nerve involvement that includes upper extremities, while the maintenance phase has more sensory sural nerve involvement, albeit more likely asymptomatic or milder. Phase-specific patterns suggest distinct pathophysiological mechanisms.